PENGARUH KOMPETENSI, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Pada Koperasi Unit Desa Pakis, Kabupaten Malang) - Syamsul Arifin; Hadi Sunaryo; M Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTION The study was conducted at KUD Pakis Malang, East Java. The purpose of this study was to examine and analyze the influence of competence, work environment and compensation for employee performance partially or simultaneously. The variables used are competence, work environment and compensation as independent variables, employee performance as the dependent variable. The samples used were 42 KUD Pakis Malang poor employees. Data collection method used is questionnaire (questionnaire). The analysis used includes instrument testing, classical assumption test, normality test, linear regression multiple regression and hypothesis testing using multiple linear regression analysis with the help of SPSS 16.0 for Windows software.The results showed that the competence had a significant effect on the performance of Pakis Malang KUD employees in East Java, the work environment had a significant effect on the performance of Pakistani KUD employees in East Java, the compensation had a significant effect on the performance of Pakistani KUD employees in East Java. So it can be concluded that competence, work environment and compensation partially or simultaneously have a significant effect on the performance of Pakistani KUD employees in East Java.Keywords: Competence, Work Environment, Compensation, and Employee Performance